ANALISIS PERILAKU HOMOSEKSUAL DITINJAU DARI TEORI KEPRIBADIAN SIGMUND FREUD - Erwin Limbong; Andarias Timbang, Iren Dwipita, Rinto Sanda, Fransiska Wensi (Jurnal Salome : Multidisipliner Keilmuan, 2024)
This writing is an analysis of homosexual behavior in terms of Sigmund Freud's personality theory. With the aim that this writing can provide new insight into homosexuality, specifically Sigmund Freud's views. This writing was done based on observations because we saw many cases that occurred in this country, namely Indonesia. Many people think that homosexuality is something that is normal and can be done by anyone who wishes to do so. Not only that, many people are also demanding their rights so that same-sex marriage can then be legalized. Based on these assumptions or thoughts, the author is interested in analyzing this case within the framework of Sigmund Freud's thinking, using a quantitative approach and focusing on data or information from books or journals as the main literature material in obtaining information related to the topic above. Through Sigmund Freud's views we can find that homosexual cases fall into the category of social deviation or not and can even be said to be legal or illegal.